1998
DOI: 10.1128/jvi.72.9.7367-7373.1998
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the Generation in Pigs of Influenza A Viruses with Pandemic Potential

Abstract: Genetic and biologic observations suggest that pigs may serve as “mixing vessels” for the generation of human-avian influenza A virus reassortants, similar to those responsible for the 1957 and 1968 pandemics. Here we demonstrate a structural basis for this hypothesis. Cell surface receptors for both human and avian influenza viruses were identified in the pig trachea, providing a milieu conducive to viral replication and genetic reassortment. Surprisingly, with continued replication, some avian-like swine vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
358
3
9

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 862 publications
(381 citation statements)
references
References 39 publications
11
358
3
9
Order By: Relevance
“…Third, there are discrepant findings in the receptor distribution in different animals. Traditionally, it is widely accepted that both a2,3-SA and a2,6-SA are abundantly expressed in the trachea of pigs [76]. However, some recent studies have found that a2,6-SA is the predominant receptor type in the upper respiratory tract of pigs [77].…”
Section: Viral and Host Factorsmentioning
confidence: 99%
“…Third, there are discrepant findings in the receptor distribution in different animals. Traditionally, it is widely accepted that both a2,3-SA and a2,6-SA are abundantly expressed in the trachea of pigs [76]. However, some recent studies have found that a2,6-SA is the predominant receptor type in the upper respiratory tract of pigs [77].…”
Section: Viral and Host Factorsmentioning
confidence: 99%
“…Human influenza strains preferentially bind to sialic acid residues linked to galactose by the ␣2,6 linkage, while avian and equine influenza strains recognize sialic acid linked to galactose by ␣2,3 linkage (Connor et al, 1994;Gambaryan et al, 1997;Matrosovich et al, 1997Matrosovich et al, , 2004Rogers and D'Souza, 1989;. Correspondingly, human respiratory epithelial cells predominantly contain ␣2,6 sialic acid-galactose linkages, while the host cells in birds and horses mainly contain ␣2,3 linkages (Couceiro et al, 1993;Ito et al, 1998;Matrosovich et al, 2004). Respiratory epithelial cells in the pig contain both ␣2,3and ␣2,6 linkages, which explains why this animal is susceptible to both human and avian influenza viruses (Ito et al, 1998).…”
Section: Virologymentioning
confidence: 99%
“…Correspondingly, human respiratory epithelial cells predominantly contain ␣2,6 sialic acid-galactose linkages, while the host cells in birds and horses mainly contain ␣2,3 linkages (Couceiro et al, 1993;Ito et al, 1998;Matrosovich et al, 2004). Respiratory epithelial cells in the pig contain both ␣2,3and ␣2,6 linkages, which explains why this animal is susceptible to both human and avian influenza viruses (Ito et al, 1998). Because of this trait, the pig is widely regarded as a potential source of new pandemic strains, since it could serve as a non-selective host in which mixed infection of avian and human strains efficiently occurs, potentially resulting in new reassortant viruses, or in which purely avian strains can adapt to human receptor recognition.…”
Section: Virologymentioning
confidence: 99%
“…Primers and probe sequences for 2009 (H1N1) qRT-PCR. The probe was designed using the sequence of A/California/04/2009 (H1N1) (FJ96513 for the emergence of new subtypes with human pandemic potential (Ito et al, 1998;Scholtissek et al, 1993). In order to recognize promptly the novel pandemic (H1N1) 2009 in swine, reducing the potential serious economic damage as well as exposure of humans to the virus, the development of a rapid and sensitive test capable of identifying and differentiating the pandemic strain from type A influenza viruses circulating in pigs is necessary.…”
Section: Tablementioning
confidence: 99%